2013
DOI: 10.1111/cpsp.12033
|View full text |Cite
|
Sign up to set email alerts
|

Wanted: Reliable and valid measures for the science of cognitive behavioral therapy dissemination and implementation.

Abstract: The dissemination and implementation of cognitive behavioral therapy (CBT) is stalled by the lack of empirical data to guide the content and evaluation of training programs. To address the questions of "What should be taught?" and "What do clinicians learn?" reliable and valid measures of therapist behaviors and practice elements are needed. The objective of this report is to identify existing CBT measures and to assess their ability to address these critical questions. We conducted a comprehensive literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 78 publications
(119 reference statements)
0
28
0
Order By: Relevance
“…As such, the procedure of using evidence-based rating systems to objectively code therapy sessions will remain the gold standard, at least until the discrepancy between raters is better understood. Simons et al (2013) identified several measures that assess clinician fidelity broadly. However, it should be noted that a combination of measures and procedures are likely necessary to carefully assess these three components of fidelity.…”
Section: Skill As a Function Of Procedural And Reflective Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…As such, the procedure of using evidence-based rating systems to objectively code therapy sessions will remain the gold standard, at least until the discrepancy between raters is better understood. Simons et al (2013) identified several measures that assess clinician fidelity broadly. However, it should be noted that a combination of measures and procedures are likely necessary to carefully assess these three components of fidelity.…”
Section: Skill As a Function Of Procedural And Reflective Knowledgementioning
confidence: 99%
“…Simons et al (2013) describe commonly endorsed urban myths about CBT, for instance, that it is too rigid, does not honor the therapeutic relationship, and does not focus on the role of emotions. For many clinicians, CBT does not appear to align with their core attitudes and values.…”
Section: Attitudes and Valuesmentioning
confidence: 99%
“…On the other hand, some studies found no significant relationships between therapist competence and outcome in the treatment of anxiety disorders (e.g., Boswell et al, 2013;Huppert et al, 2001). However, inappropriate methodological approaches, like the evaluation of therapist competence with only one global item might be responsible for the heterogeneous findings in research (Simons et al, 2013;Webb et al, 2010;Weck et al, 2011a). There is no consistent evidence which supports that therapist adherence impacts therapy outcome (Baldwin and Imel, 2013;Webb et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, research suggests that clinicians may not use full-package, complex EBPs due to the burden associated with training, negative attitudes toward manuals or protocols, and beliefs that these EBPs may not be appropriate for clients in the settings in which they practice (e.g., Simons, Rozek, & Serrano, 2013). Moreover, research indicates that even if initially implemented with success, these complex EBPs are not likely to be sustained over time (Stirman et al, 2012).…”
mentioning
confidence: 99%